Brass–iron couple and brass–iron–wood ternary system of metal objects from the Akko 1 shipwreck (Israel). (September 2016) - Ashkenazi, D.; Inberg, A.; Langgut, D.; Hendler, N.; Cvikel, D.
Highlights: A flintlock musket and a brass case were retrieved from the Akko 1 shipwreck. These finds represent galvanic brass–iron and complex brass–iron–wood systems. In both objects the iron was sacrificed to protect the brass and the wood. Abstract: A flintlock musket and a brass case with two nails attached, were retrieved from the Akko 1 shipwreck, dated to the early 19th century, and studied using metallurgical analysis. Both artefacts were covered with encrustation and concretion. The iron musket barrel and the iron nails did not survive; only corrosion products and oxides were left of them. The brass case, the brass musket ramrod pipe, and the wood texture were well preserved. In both artefacts the iron was sacrificed to protect the brass. This information may assist in future conservation of similar objects.